An assessment of factors associated with shisha smoking among students at Evelyn Hone College, Lusaka, Zambia - Loloji, Brian; Munsanje, Foster; Haakonde, Titus; Samanyama, Mwanamwaka (International Journal Of Community Medicine And Public Health, 2020)
Background: Shisha smoking in Zambia, referring to the way of smoking tobacco in which the vapor passes through water before inhalation, is seen as a new practice, especially among youths of 18 to 25 age group. Factors associated with this practice have not yet been established. This study aimed at assessing the factors associated with shisha smoking among students at Evelyn Hone College. Methods: A cross-sectional study was conducted on 347 Evelyn Hone College students selected using convenience sampling method. Data collection was by pre-tested semi-structured questionnaires. Chi-squared statistical tests were used to determine the association between the independent variables, which were demographic, social, environmental, cultural and personal factors, and the dependent variable being shisha smoking using SPSS version 18. Results: The study revealed that shisha smoking was significantly associated with age of the smoker, level of income, peer pressure and knowledge levels of the smokers on adverse effects associated with shisha smoking. These relationships were determined by the logistical regression output which showed that age [OR=1.802 (1.152-2.818), p<0.05)], friends smoke cigarette/shisha [(OR=4.417 (1.760-11.086), p<0.05)], monthly allowance/income [(OR=0.663 (0.456-0.965), p<0.05)] and perceived risk [(OR=0.084 (0.046-0.154), p<0.05)] which all showed significant association with shisha smoking. Conclusions: Interventions to reduce or quit shisha smoking among students need to have extended policies that apply to cigarette smoking. Additionally, health education campaigns against shisha smoking should as well be packaged in the anti-smoking messages targeting the youths.